Ductility performance of Thin-Walled Composite-Filled (TWFC) beam at internal support / Mohd Asha'ari Masrom - Masrom, Mohd Asha'ari (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
Ductility of reinforced structures is a desirable property where resistance to brittle failure during flexure is required. The most influential parameter towards the ductility value is the ratio of steel area to concrete area. However, the study on ductility performance of TWCF beam is still lacking. This paper aims is to reveal the ductility performance of Thin-Walled Composite-Filled Beam under flexural test. This paper presents a laboratory work which involves three samples of TWCF beams with different strength-enhancement devices. The effects of various modes interface connections are co-related to the generation of shear bond between sheeting and concrete, using both experimental and theoretical results. The strength and failure modes of the beams are found to be dependent on the interface connections. Analytical models for the ductility design of beams are developed and their performance is validated through experimental results using partial shear connection. The beams were designed by considering whether the strength will be governed by buckling or yielding of the steel plate. The analytical ductility model of TWCF beam shows a good agreement with the experimental result.